Peramalan Jumlah Produksi Kerupuk Kamang Berdasarkan Keuntungan Hasil Produksi Menggunakan Analisis Regresi Invers dengan Metode Klasik - yulistia rahmadani; Helma Helma (Journal of Mathematics UNP, 2021)
The  limitation  of  kamang  cracker  businessmenin  marketing  their  products  is  the main factor  that  makes  businessmenunable  to maximizethe  profits  of  theirproduction.    To  maximize profits, a method is needed to predict the number of kamang crackers that must be produced based on the  profits  obtained. In this  case,  regression  analysis  with  classical  method  can  be  used  wherethe value of x0 can be predicted based on the dependent variable y0. The purpose of this study is to create a  model  and  determine  the  prediction  interval  from  forecasting the  numberofkamang  cracker production based on the profit obtained from the production. The data used are primary data obtained from 25 business houses inKecamatanKamang Magek .  From the prediction results obtained, it can be interpretationthe number of kamangcrackers that must be produced